Cell parts to complex processes, from the bottom up. (8th November 2018) - Good, Matthew; Trepat, Xavier
Engineering approaches allow biological structures and behaviours to be reconstitutedin vitro . A biologist and a physicist discuss the potential and limitations of this bottom-up philosophy in providing insights into complex biological processes. The limits of bottom-up biology debated.